Novel approaches targeting ferroptosis in treatment of glioma - Zhao, Jing; Zang, Fengling; Huo, Xiaoya; Zheng, Shengzhe (Frontiers in Neurology, 2023)
Glioma is a malignant brain tumor with a high mortality rate; hence novel treatment approaches are being explored to improve patient outcomes. Ferroptosis, a newly described form of regulated cell death, is emerging as a potential therapeutic target in glioma. Ferroptosis is characterized by the accumulation of lipid peroxides due to a loss of intracellular antioxidant systems represented by the depletion of glutathione and decreased activity of glutathione peroxidase 4 (GPX4). Since glioma cells have a high demand for iron and lipid metabolism, modulation of ferroptosis may represent a promising therapeutic approach for this malignancy. Recent studies indicate that ferroptosis inducers like erastin and RSL3 display potent anticancer activity in a glioma model. In addition, therapeutic strategies, including GPX4 targeting, lipid metabolism modulation, inhibition of amino acid transporters, and ferroptosis targeting natural compounds, have shown positive results in preclinical studies. This review will provide an overview of the functions of ferroptosis in glioma and its potential as a suitable target for glioma therapy.